The Comparison of Chunking Methods to Enhance the Cognitive Capacity of Short-term Memory to Retain Textual Information among High School Students - Suppawittaya, Piwat; Yasri, Pratchayapong (Universitas Terbuka, 2021)
Our short-term memory has a limited capacity of taking in information and retaining it the memory storage. However, this can be enhanced by various memory techniques especially dividing the information into smaller chunks. To investigate this memory enhancement strategy, this study compared the effectiveness of three chunking methods, namely One-Chunk, Two-Chunk, and Three-Chunk to enhance the capacity to retain information in the forms of letters and numbers in the short-term storage. Participants in this study were 50 high school students who took part in an experimental design of online short-term memory assessment. The results revealed that the ability to remember 10 distinct alphabets and 10 distinct digits statistically varied, depending on how the information was chunked. To be more precise, the student participants could memorize the information when divided into 2 or 3 chunks more effectively than one full set of the information (1 chunk) as the mean scores gained in the two chunking methods were statistically greater than that of the One-Chunk delivered information. However, the findings only relied on single types of information so that further research could be done to explore this with more complicated information. Educational implications can be drawn from this present study that in order to assist students to memorize and retain learning materials more effectively, it is essential to help classify them into 2-3 groups of information. This could be done through the use of tree thinking, binary thinking, and computational thinking.